Unlocking the application potential of forward osmosis through integrated/hybrid process - Daniel Johnson (Science of The Total Environment, 2020)
Study of forward osmosis (FO) has been increasing steadily over recent years with applications mainly focusing on desalination and wastewater treatment processes. The working mechanism of FO lies in the natural movement of water between two streams with different osmotic pressure, which makes it useful in concentrating or diluting solutions. FO has rarely been operated as a stand-alone process. Instead, FO processes often appear in a hybrid or integrated form where FO is combined with other treatment technologies to achieve better overall process performance and cost savings. This article aims to provide a comprehensive review on the need for hybridization/integration for FO membrane processes, with emphasis given to process enhancement, draw solution regeneration, and pretreatment for FO fouling mitigation. In general, integrated/hybrid FO processes can reduce the membrane fouling propensity; prepare the solution suitable for subsequent value-added uses and production of renewable energy; lower the costs associated with energy consumption; enhance the quality of treated water; and enable the continuous operation of FO through the regeneration of draw solution. The future potential of FO lies in the success of how it can be hybridized or integrated with other technologies to minimize its own shortcomings, while enhancing the overall performance.